Combination of zero-valent aluminum-acid system and electrochemically activated persulfate oxidation for biologically pre-treated leachate nanofiltration concentrate treatment. (1st March 2023) - Yazici Guvenc, Senem; Ozen, Irem; Binici, Miray; Yildirim, Doga; Can-Güven, Emine; Varank, Gamze
Abstract: This study investigated the performance of combined zero-valent aluminum (ZVAl) and electrochemically activated persulfate (PS) oxidation for the leachate nanofiltration concentrate (NFC) treatment. Firstly, operating parameters in the ZVAl procedure were optimized and under the optimum conditions (ZVAl dose 1 g/L, initial pH 1.5) the removal efficiency of the chemical oxygen demand (COD), UV254, and color were 22.39%, 29.03%, and 48.26%, respectively. Secondly, the effect of various anode types (Ti/RuO2, Ti/IrO2, and Ti/SnO2 ) within the electrooxidation (EO) process was evaluated. The Ti/RuO2 anode was found to be the most effective one in terms of pollutant removal efficiencies and operation cost. The efficiency of single, binary, and hybrid processes was evaluated by control experiments and the results were ranked as PS < ZVAl < ZVAl + PS < EO < EO + PS < EO + ZVAl < EO + ZVAl + PS. In the following part of the study, the Box-Behnken design was preferred to optimize the operating parameters of the hybrid EO + ZVAl + PS process. The COD, UV254, and color removal efficiencies under optimum conditions (4.88 mM PS dose, 1.6 A current applied, and 120 min reaction time) were 62.1%, 75.2%, and 99.9%, respectively. The estimated and experimentally obtained data were close to each other. The pollutant removal efficiencies increased in parallel with the current density and reaction time; however, the effect of the PS dose remained at a negligible level. The obtained results indicate the effectiveness of the hybrid EO + ZVAl + PS process for the treatment of leachate nanofiltration concentrate under optimized conditions. Graphical abstract: Image 1 Highlights: The hybrid EO + ZVAl + PS process was optimized. The highest reaction rate constant for COD is 0.0061 1/min with the EO + ZVAl + PS process. The optimum conditions were 4.88 mM PS dose, 1.6 A applied current, and 120 min. COD, UV254, and color removals were 62.1%, 75.2%, and 99.9%, respectively.